Association Mapping of Early Mortality Syndrome - Acute Hepatopancreatic Necrosis Disease Tolerance in Litopenaeus vannamei - Nimlamai, Anong; Khanbo, Supaporn; Wirojsirasak, Warodom; Ukoskit, Kittipat (Science & Technology Asia, 2025)
Early Mortality Syndrome (EMS)-Acute Hepatopancreatic Necrosis Disease (AHPND) is a severe bacterial disease that significantly impacts Pacific white shrimp (Litope naeus vannamei) farming, leading to substantial declines in shrimp production. To mitigate losses caused by EMS-AHPND, molecular breeding presents a promising approach for sustainable disease prevention. This study focused on the identification of single nucleotide polymorphism (SNP) markers associated with EMS-AHPND phenotypes using Genotyping by-sequencing (GBS). SNP markers were identified in fourth-generation selective breeding lines of L. vannamei. A total of 9,504 filtered SNPs were analyzed for their association with EMS-AHPND phenotypes using the Fixed and Random Model Circulating Probability Unification (FarmCPU), accounting for population stratification and cryptic relatedness. Seven SNPs were identified as significantly associated with EMS-AHPND phenotypes, with P-values passing the Bonferroni-adjusted threshold. This study provides a valuable genetic tool for the genetic improvement of EMS-AHPND tolerance in L. vannamei.